2018
DOI: 10.1111/lcrp.12138
|View full text |Cite
|
Sign up to set email alerts
|

Imposter identification in low prevalence environments

Abstract: Purpose Travel document screeners play an important role in international security when determining whether a photograph ID matches the tendering individual. Psychological research indicates when conditions involve low base rates of ‘imposter’ photographs, document screeners change their response criterion for rendering a ‘match’ determination. The primary purpose of the current experiments was to examine the nature of this base rate criterion shift, free from experimental bias, for both own‐ and other‐race fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Unlike Experiment 1, Experiment 2's paradigm resulted not only in differences in criterion, but also discriminability, by mismatch prevalence. These findings align well with other recent LPE studies in the facial-identification literature (e.g., Papesh et al, 2018;Papesh & Goldinger, 2014;Susa et al, 2019) and perhaps explain the lack of an effect in others (e.g., Bindemann et al, 2010;Stephens et al, 2017). This latter study and others like it used image sets with low between-person variability (e.g., Glasgow Face Matching Test; Burton et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Unlike Experiment 1, Experiment 2's paradigm resulted not only in differences in criterion, but also discriminability, by mismatch prevalence. These findings align well with other recent LPE studies in the facial-identification literature (e.g., Papesh et al, 2018;Papesh & Goldinger, 2014;Susa et al, 2019) and perhaps explain the lack of an effect in others (e.g., Bindemann et al, 2010;Stephens et al, 2017). This latter study and others like it used image sets with low between-person variability (e.g., Glasgow Face Matching Test; Burton et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…More recent work has added to our understanding of the LPE by using face databases containing images taken Note: a Indicates a significant difference at p < .017, corrected for multiple comparisons multiple days (if not years in some instances) apart, (Papesh and Goldinger, 2014;Papesh et al, 2018) and another recent study (Susa, Michael, Dessenberger, & Meissner, 2019) found the LPE. This latter study used images specifically designed to test cross-race influences, and, therefore, portrayed a wider-degree of within-and between-person variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unusual nonverbal behaviour is by definition infrequent, necessitating a constraint on the number of trials that were available for this condition. In addition, mismatches also occur much less frequently than identity matches in passport control settings and must therefore share the infrequency characteristic of unusual body language (e.g., Bindemann et al., 2010 ; Papesh & Goldinger, 2014 ; Susa et al., 2018 ). There are several reasons, however, for why the trial count for unusual body language and mismatches cannot explain the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that unusual body language that differs from the majority of passengers might be seen as a specific indicator that an identity impostor is present. While the detection of these mismatching face pairings is a specific concern for person identification at passport control, these cases also occur with less frequency than identity matches ( Bindemann et al., 2010 ; Fysh & Bindemann, 2017b , 2018a; Papesh & Goldinger, 2014 ; Susa et al., 2018 ). In the experiments reported here, mismatch frequency was therefore also kept low.…”
mentioning
confidence: 99%